Longevity of antibody responses is associated with distinct antigen-specific B cell subsets early after infection - Lisan H. Kuijper; Christine Kreher; George Elias; Mathieu Claireaux; Mathieu Claireaux; Gius Kerster; Gius Kerster; Amélie V. Bos; Mariël C. Duurland; Veronique A. L. Konijn; Alberta G. A. Paul; Alberta G. A. Paul; et al. (Frontiers in Immunology)
IntroductionUpon infection, T cell-driven B cell responses in GC reactions induce memory B cells and antibody-secreting cells that secrete protective antibodies. How formation of specifically long-lived plasma cells is regulated via the interplay between specific B and CD4+ T cells is not well understood. Generally, antibody levels decline over time after clearance of the primary infection.MethodIn this study, convalescent individuals with stable RBD antibody levels (n=14, “sustainers”) were compared with donors (n=13) with the greatest antibody decline from a cohort of 132. To investigate the role of the cellular immune compartment in the maintenance of antibody levels, SARS-CoV-2-specific responses at 4 to 6 weeks post-mild COVID-19 infection were characterized using deep immune profiling.ResultsBoth groups had similar frequencies of total SARS-CoV-2-specific B and CD4+ T cells. Sustainers had fewer Spike-specific IgG+ memory B cells early after infection and increased neutralizing capacity of RBD antibodies over time, unlike the declining group. However, declining IgG titers correlated with lower frequency of Spike-specific CD4+ T cells.ConclusionThese data suggest that “sustainers” have unique dynamics of GC reactions, yield different outputs of terminally differentiating cells, and improve the quality of protective antibodies over time. This study helps identify factors controlling formation of long-lived PC and sustained antibody responses.